STRATEGI KEBUDAYAAN LOKAL DALAM IMPLEMENTASI NILAI MODERASI BERAGAMA (Kajian Seni Pertunjukkan Wayang Golek Cepak) - Dodi Kurniawan; Jamali; Suteja (HUMANITIS: Jurnal Homaniora, Sosial dan Bisnis, 2023)
Moral and character education is increasingly being neglected with the presence of digitalization developments. There needs to be innovation in the direction of education so that the character and morals of the generation are more towards national education goals. The presence of local culture in a lesson is a learning model that prepares students with morals and character formed from cultural education. The aims of the study: (1) to know the values of religious education contained in the plays of wayang golek cepak, (2) to know the analysis of wayang golek performances as a learning material strategy for religious moderation, and (3) to know the implementation of the art of wayang golek performances as a implementation of the values of religious moderation. This study used a qualitative approach to social phenomenology, the data collected came from literature reviews and interview documentation, namely data that came from interviews with various sources and a review of library materials, in the form of: encyclopedias, books, articles, and scientific papers published in mass media such as magazines, newspapers and scientific journals as well as research conducted by going directly to the field without going through the information media to obtain the results of character education development in the values of local culture-based religious moderation. The results of this study are: (1) In-depth observation of the cepak wayang golek shows that it is not a performing art that aims for biological satisfaction, but provides inner satisfaction (spectacle-guidance-order). (2) the implementation of learning refers more to the achievement of the development and character development of students determined through an attitude or affective assessment. (3) the development of local cultural education in the implementation of religious moderation values has 8 main character pillars as a reference for student achievement.